Detergent‐Compatible Robust Alkaline Protease from Newly Isolated Halotolerant Salinicoccus sp. UN‐12. Issue 6 (25th September 2017) - Mokashe, Narendra; Chaudhari, Bhushan; Patil, Ulhas
Abstract: Currently, enzyme‐containing blended detergent preparations are favored in the detergent industry. The detergent compatibility of an enzyme depends on its robustness to withstand harsh operating conditions and maintain efficient functioning in the presence of various surfactants and detergents. Alkaline proteases from halotolerant microbes having the capability to work in demanding environments are desirable for their application in the detergent industry. The protease secreted by a halotolerant soil isolate Salinicoccus sp. UN‐12 was evaluated for its suitability in detergent formulations. The studied enzyme is an alkaline serine protease (63 kDa) with an optimum temperature of 55 °C and optimum pH of 8.5. The protease was purified 17‐fold with a 4% yield. The protease was active in NaCl (up to 4 mol) and showed enhanced activity in the presence of CaCl2, KCl, and MnCl2 . In addition, the proteolytic activity was sustained in the presence of various organic solvents, cyclodextrin, disodium cocoamphodiacetate, ionic liquids, hydrotropes, and ultrasound. This report is the first to document the multifarious robustness and novel attributes of a protease secreted by the newly isolated Salinicoccus sp. UN‐12. The protease‐detergent formulation efficiently removes blood, egg, grass, and tomato sauce stains. This protease is now available for efficient and eco‐friendly applications in the detergent industry. Graphical Abstract: